Transcatheter closure of ventricular septal defects using the Amplatzer Duct Occluder II device: a single-center experience - Polat, Tugcin Bora; Türkmen, Esma (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2016)
Introduction: Off-label use of different devices has been described for percutaneous closure of ventricular septal defects (VSD) because of the unacceptable rate of post-procedure heart block associated with special VSD devices. Aim : To describe the early single-center clinical experience with closure of a VSD using the Amplatzer Duct Occluder II (ADO II) device in children. Material and methods : Between May 2013 and June 2015, 26 patients between 13 days and 16 years of age underwent percutaneous closure of a VSD with an ADO II device at our institute. The decision to use the ADO II device was based primarily on lower risk of total atrioventricular block (TAVB) after VSD closure reported in the literature, reduction of the cost of the procedure and the need to close symptomatic VSDs in young patients. Results : The location of the VSD was perimembranous in 21 patients, postsurgical residual in 2, midmuscular in 2 and apical muscular in 1. Complex procedures including newborn, combined procedures and postsurgical residual VSD were performed in 5 (19%) patients. The median duration of follow-up was 12 months. The complete VSD closure rate was 81% immediately after the procedure, 85% at 24 h, and 93% at the last follow-up. There was no device embolization. During the entire follow-up period, TAVB did not develop. Conclusions : The ADO II constitutes a safe and effective therapeutic alternative for morphologically varied VSDs in all pediatric age groups. A larger range of sizes and configurations of this occluder may be required to successfully occlude a wider range of VSDs.